Design and prototyping of UAVs with deployable structures, underwater quadcopter : acquaflyer - Kee, Han Chong (2015)
A specific type of Unmanned Ariel Vehicles (UAV) has been gaining popularity over the years. This UAV is classified as quadcopters. A quadcopter is easily recognised by its cross-shaped frame and four motors fitted with propellers. This project seeks to identify, design and build a new quadcopter UAV. The idea: to build a hybrid quadcopter that is able to both fly in air and dive into water. The working principles, detailed design, prototyping phases as well as challenges and limitations are discussed in this report. The final prototype, Acquaflyer achieved its objective of a hybrid quadcopter.